Utilizing coriander as a natural remedy for combating Eimeria papillata infection and oxidative stress in mice - Heba Ismaeil; Nabila M. Mira; Saeed El-Ashram; Mohamed A. Dkhil; Rewaida Abdel-Gaber; Shaimaa M. Kasem (Journal of Taibah University for Science)
Coccidiosis, an intestinal disease caused by Eimeria spp., poses significant economic challenges globally, primarily due to the development of drug resistance from the prolonged use of anticoccidial medications. The recent use of botanicals as an alternative to coccidiostats has become an appealing approach for controlling coccidiosis. Therefore, this study investigated the impact of Coriandrum sativum leaf extracts (CSE) on Eimeria papillata-infected mice, evaluating its potential as an alternative treatment. Phytochemical analysis of CSE was conducted using Fourier Transform Infrared spectroscopy. Thirty male Swiss albino mice were divided into five groups (G) as follows; G1: a negative control (uninfected, untreated), G2: a CSE-only group, G3: an untreated infected group, G4: an infected group treated with CSE, and G5: an infected group treated with amprolium, a common anticoccidial drug. G3 to G5 were inoculated with 1 × 10³ sporulated E. papillata oocysts and treated for five days. Post-treatment evaluations included oocyst excretion, body weight changes, feed intake, and histopathological examination. The results indicated that CSE dramatically decreased oocyst output to 75.42 × 10³±5.57 OPG, in contrast to the infected group, which exhibited 234.17 × 10³±20.72 OPG. CSE treatment improved body weight, feed consumption and reduced parasitic stages in jejunal tissue. CSE decreased oxidative damage by decreasing NO and MDA levels, while enhancing GSH and SOD. Moreover, CSE treatment led to decreased levels of the inflammatory cytokines IL-10, IFN-γ, TNF-α, and iNOS.In conclusion, CSE has promise as a natural anticoccidial drug with antioxidant and anti-inflammatory attributes, necessitating additional research to comprehensively elucidate its therapeutic processes.